A novel method for the detection of liver damage using fluorescence of hepatic mitochondria in a rat model following ischaemia/reperfusion injury of the small intestine. Issue 4 (2011) - Tomečková, Vladimíra; Štefanišinová, Miroslava; Bilecová-Rabajdová, Miroslava; Kriššáková, Eliška; Tomečko, Marián; Tóth, Štefan; Pekárová, Tímea; Mareková, Mária
Abstract : We present a novel method of assessing damage to the liver using fluorescence analysis of hepatic mitochondria following ischaemia/reperfusion of the small intestine in a rat model. This work is of substantial importance in understanding the syndrome of multiorgan failure after ischemia/transplantation of the small intestine. Mitochondria were isolated from six sample groups that had undergone three different experimental treatments: a control group; a treatment with ischaemia followed by reperfusion of the small intestine (IRx ); and, a one hour ischaemia followed by reperfusion after transplant of the small intestine (TRx ). The IR treatment was further subdivided into three groups: 1, 24 h and 30 days reperfusion – IR1, IR24, IR720, respectively. Concomitantly, the TR treatment was further subdivided: one group underwent a 1 h reperfusion and another group a 6 h reperfusion following ischaemia and transplant – groups TR1 and TR6, respectively. Once treatment had been undergone, mitochondria were isolated and all five experimental groups – IR1, IR24, IR720, Tr1, Tr6 – and their emission matrices were analysed compared with that of the control group (C). Comparing fluorescence values in zone A of all experimental groups with those of the control group indicated a reduction in aromatic amino acids in the mitochondria of all experimental groups. Comparison of fluorescent zone B of experimental groups with the control group identified a lack of oxygen in samples IR1, IR24, which was indicated though an increase in the fluorescence of the reduced pyridine nucleotide NADH+H + .